Effects of neutrophil granule proteins on sepsis-associated lymphopenia and their relationship with CD4+ T-cell pyroptosis - Mao, Jia-yu; Xie, Ya-wen; Lei, Xian-li; Zhang, Jia-hui; Cheng, Wei; Cui, Na (Frontiers in Immunology, 2025)
BackgroundNeutrophil acts as a double-edged sword in the immune system. We hypothesized that an elevated neutrophil granule protein level is associated with sepsis-associated lymphopenia (SAL).MethodsWe enrolled 61 patients with sepsis admitted to the Department of Critical Care Medicine of Peking Union Medical College Hospital between May 2022 and October 2023 in this study. Clinical and immunological parameters were recorded. Levels of neutrophil granule proteins, including myeloperoxidase (MPO) and neutrophil elastase (NE), and pyroptosis factors were examined.ResultsLevels of neutrophil granule proteins (MPO, 82.9 vs. 175.3, p < 0 <.0001; NE, 56.3 vs. 144.2, p < 0.0001) were significantly higher in patients with sepsis with lymphopenia. Neutrophil granule protein levels were independently associated with SAL risk (MPO: OR = 1.0841, 95% CI, 1.0020–1.1730; NE: OR = 1.0540, 95% CI, 1.0040–1.1065). The area under the curve of MPO levels predicting SAL occurrence was 0.939 (95% CI, 0.846–0.984), and that of NE was 0.950 (95% CI, 0.862–0.989). Furthermore, neutrophil granule proteins were significantly correlated with CD4+ T cell and its pyroptosis [MPO and CD4+ T cells (r = −0.4039, p < 0.0001), CD4+NLRP3 (r = 0.4868, p < 0.0001), NE and CD4+ T cells (r = −0.5140, p < 0.0001), and CD4+NLRP3 (r = 0.6513, p < 0.0001)].ConclusionIncreased levels of neutrophil granule proteins were significantly associated with SAL incidence, and a significant relationship between neutrophil granule proteins and the pyroptosis pathway of CD4+ T cells was revealed.Clinical trial registrationchictr.org.cn identifier ChiCTR-ROC-17010750.